Interleukin-17 Blockade Leads to Shifts from Stage-based Towards Response-based Disease Clusters- Comparative Data from Very Early and Established Psoriatic Arthritis - Kampylafka, Eleni; Tascilar, Koray; Lerchen, Veronika; Linz, Christina; Sokolova, Maria; Zekovic, Ana; Kleyer, Arnd; Simon, David; Rech, Jürgen; Sticherling, Michael; Schett, Georg; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Secukinumab leads to shifts from stage-based towards response-based disease clusters-comparative data from very early and established psoriatic arthritis - Kampylafka, Eleni; Tascilar, Koray; Lerchen, Veronika; Linz, Christina; Sokolova, Maria; Zekovic, Ana; Kleyer, Arnd; Simon, David; Rech, Jürgen; Sticherling, Michael; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2020)
Background: Limited information exists about the very early forms of psoriatic arthritis. In particular, differences and responsiveness of patient-reported outcomes (PROs) in very early as compared to established PsA have not been investigated to date. Methods: Cross-sectional and prospective longitudinal evaluation of PROs related to pain (VAS), physical function (HAQ-DI, SF-36 physical), mental function (SF-36 mental), impact of psoriatic skin (DLQI), joint (PsAID), and global disease (VAS) in two small prospective observational studies on secukinumab 300 mg over 6 months in very early disease patients (IVEPSA study, N = 20) and established PsA (PSARTROS study, N = 20). Cluster analysis was performed at baseline and 24-weeks of follow-up. Results: While responses in pain and physical activity-related PROs to secukinumab were more pronounced in established PsA than a very early disease, effects on PROs related to general health perception, as well as those related to emotional and mental well-being, were modified in a similar way in very early disease and established PsA. Cluster analysis based on global disease activity and PROs showed that baseline clusters reflected very early disease and established PsA, while after secukinumab treatment these clusters were abolished and new clusters based on differential responses to physically and mentally oriented PROs formed. Conclusions: Inhibition of IL-17A by secukinumab leads to comprehensive improvement of general health perception and mental well-being in very early and established PsA, while overall responses in pain and physical activity are more pronounced in established disease. Most importantly, treatment restructures the original patients' clusters based on disease stage and leads to the formation of new clusters that reflect their response in physical and mental-orientated PROs. Trial registration: NCT02483234, registered 26 June 2015, retrospectively registered.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Cluster analysis; IL-17A; Psoriatic arthritis; Quality of life; Secukinumab